Analisis Pengaruh Product Quality, Perceived Value & Efek Moderasi Frekuensi Mengikuti terhadap Trust to Product pada Live Shopping - Alfan Azizi; Diah Priharsari; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The development of information technology is currently changing the way people shop, giving rise to new behaviors in online shopping. This has prompted businesses to adopt various selling methods, one of which is live shopping on social media or e-commerce platforms. Live shopping involves using video to introduce and promote products, with the aim of influencing consumers' trust in the product. Trust in a product can be influenced by factors such as product quality, perceived value, and the frequency of participation in live shopping activities. This study aims to determine the influence of these factors on trust in a product during live shopping, using a quantitative approach and Structural Equation Modeling-Covariance Based (SEM-CB) method. The researchers distributed online surveys and collected clean data from 433 respondents. Data processing was performed using IBM SPSS 22 and IBM AMOS 26 tools. The results of the study showed that one hypothesis was not accepted: that product quality has an influence on trust in the product, with a probability (p) value of 0.805. In this case, the audience may not necessarily trust the product quality when live shopping activities on social media and e-commerce.